THE INFLUENCE OF THE NUMBERED HEAD TOGETHER MODEL ON STUDENTS’ LEARNING OUTCOMES - Salsabila Marretta; Hetilaniar; Marleni (Universitas PGRI Palembang, 2024)
This research is motivated by low student learning outcomes, because in the teaching and learning process teachers only use conventional learning models, so it is less interesting for students to pay attention to. This research aims to determine the influence of the Numbered Head Together model on English Subject learning outcomes on State Emblem material at SD Negeri 43 Palembang. This research is a type of experimental research, Quasi Experimental Design. The population and sample in this study were class III students at SD Negeri 43 Palembang, totaling 16 students in the control class and 14 students in the experimental class. Data collection techniques in this research are observation, tests, and documentation. The data analysis techniques in this research are normality test, homogeneity test and hypothesis test. From the results of calculating the hypothesis test using the independent sample t-test, the Sig.(2-tailed) value was 0.000 < 0.05 and the value of tcount > ttable was 5.145 > 1.701, which means that based on hypothesis testing Ho was rejected and Ha was accepted. This means that there is an influence of the Numbered Head Together model on learning outcomes in the State Emblem material at SD Negeri 43 Palembang.